PENGARUH LEVERAGE, LIKUIDITAS, UKURAN PERUSAHAAN, INFLASI DAN PROFITABILITAS (Studi Pada Perusahaan Properti, Real Estate and Building Contruction Terdaftar di Bursa Efek Indonesia) - ISTYAWATI, NOVIA; PURWOHANDOKO (Jurnal Ilmu Manajemen (JIM), 2019)
This study aims to see the effect of leverage, liquidity, firm size and inflation the profitability. The population in this study are 35 Property, Real Estate, and Building Construction listed in Indonesia Stock Exchange and the sample used in this research is purposive sampling. The analysis method used is multiple linear regression analysis. The results of analysis through hypothesis testing, simultaneously leverage, liquidity, firm size and inflation joint influence on profitability. Partially, shows that leverage does not affect probability., liquidity affects profitability., No unemployed funds will increase profitability. Company size does not affect profitability., Assets not used optimally do not affect profitability. Inflation has an effect on profitability., The price of goods increases will reducw the value of inflation. Keywords: firmsize; inflation; leverage; profitability.